A new squat lobster (Crustacea: Decapoda: Anomura: Chirostylidae) from off NW Spain - Baba, Keiji; Macpherson, Enrique (Zootaxa, 2012)
Uroptychus cartesi, a new species of squat lobster belonging to the family Chirostylidae, is described based upon materialrecently collected from the Bank of Galicia, a deep seamount located off north-west Spain. This is now the fifth speciesof the genus known from the eastern Atlantic. The four species previously recorded in the region (U. bouvieri, U. concolor,U. maroccanus and U. rubrovittatus) are morphologically rather remote from the new species. The spinose carapace lat-eral margin links U. cartesi to U. bouvieri but the other characters displayed by the new species are largely different fromthose of that species. Uroptychus cartesi is distinguished from U. bouvieri by the epigastric region having denticles ar-ranged in small arcs transversely rather than a pair of spines behind the eyes; the anterolateral spine of the carapace ismuch larger than, instead of subequal to, the lateral orbital spine; the P2–4 propodi are slightly more than half, instead oftwice, the length of dactyli; and the penultimate flexor marginal spine of P2–4 dactyli are twice as broad as, rather than as broad as the antepenultimate spine. A key to the species of Uroptychus from the eastern Atlantic is provided.